Knowledge Field Activity of Industry-University-Research Alliance on 5G Knowledge Flow and 5G Technology Innovation Performance - Zhang, Peng; Zhou, Jianming (Big Data Analytics for Cyber-Physical System in Smart City, 2021)
This paper studies how knowledge field activity of industry-university-research alliance affect researcher’s 5G technology innovation performance through promoting alliance’s 5G knowledge flow, and samples 103 researchers from 10 Chinese enterprise or university labs in Shenzhen and Beijing for empirical research. The empirical results found that (1) knowledge field activity of industry-university-research alliance had direct positive affect on 5G knowledge flow containing with both volume of 5G knowledge flow and precision of 5G knowledge flow, and researcher’s 5G technology innovation performance significantly; (2) 5G knowledge flow including both volume of 5G knowledge flow and precision of 5G knowledge flow had direct positive affect on researcher’s 5G technology innovation performance significantly, and meanwhile mediated the direct effect of knowledge field activity of industry-university-research alliance on researcher’s 5G technology innovation performance.